A full-range-360° resolver-to-DC converter - Kaewpoonsuk, Anucha; Kamsri, Thawatchai; Petchmaneelumka, Wandee; Riewruja, Vanchai (My University, 2007)
In this paper, a triangular-to-sawtooth waveform converter and a control logic circuit have been described. Using two designed circuits connected with OTA-based sine-to-triangular wave converter and demodulator, a resolver-to-DC converter is proposed. The converter linearly produces output signal proportional to the shaft angle in full range of 360°. Experimental results verifying the performances of the proposed converter circuit agree well with the theoretical prediction. ©ICROS.
Keywords: Arcsine function circuit and sine-to-triangular converter; Inverse-sine function circuit; Resolver converter